Rancang Bangun Folding Scooter Electric (E-Scooter) - Tianur, Tianur; Putra, Dicky Herlangga; Rahmawaty, Made (Universitas Muhammadiyah Metro, 2023)
Electric scooter is a short distance transportation tool that is used to make it easier for humans to move from one place to another. This transportation tool is designed as a means of transportation that is easy to carry, does not require large space for storage, is efficient and environmentally friendly. The E-Scooter is designed with a collapsible frame to make it easier for users to carry and store it. The E-Scooter has dimensions of 780 mm in length and 800 mm in height, besides that the speed of the E-Scooter can be adjusted according to the needs of its users and can be used in general. Brushless DC motors are used as the prime movers because they are efficient, environmentally friendly and suitable for electric vehicles. This E-Scooter also uses a UPS battery as its power source, so that users can drive a scooter at any time for long trips. if the UPS battery power runs out, the UPS battery can be recharged using a charger. The Brushless DC motor drives the sprocket and rear wheel on the E-Scooter. This E-Scooter can carry a maximum load of 80 kg. The speed that can be achieved is 16 km/hour on flat road conditions, and 11 km/hour on uphill roads. the duration of using this E-Scooter can reach 18 minutes of normal use on a good and uphill road surface.